2016
DOI: 10.1038/cgt.2016.55
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of HOXB7 protein reduces sensitivity of oral cancer cells to chemo-radiotherapy

Abstract: The upregulation of homeobox-B7 (HOXB7) in cancers has been reported. However, its role in oral cancer progression remains to be investigated. In current study, our data revealed that reconstitution of HOXB7 expression by transient transfection resulted in increased cell growth, migration and invasion in vitro. In addition, apoptosis and clonogenic assay data showed that overexpression of HOXB7 decreased the sensitivity of oral cancer cells to vincristine-induced apoptosis of HSC-4 and KB/VCR cells. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Another research suggested that Wnt signaling was also involved in TGF-␤-mediated fibrosis (57). Similarly, HOXB7 overexpression advanced oral cancer cell migration via the activation of the transforming growth factor ␤2/SMAD3 signaling pathway (54). This supporting evidence and reported studies offer the basis in demonstrating the possible link between both HOXB7 and the Wnt/␤-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 61%
“…Another research suggested that Wnt signaling was also involved in TGF-␤-mediated fibrosis (57). Similarly, HOXB7 overexpression advanced oral cancer cell migration via the activation of the transforming growth factor ␤2/SMAD3 signaling pathway (54). This supporting evidence and reported studies offer the basis in demonstrating the possible link between both HOXB7 and the Wnt/␤-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 61%
“…Homeobox B7 (HOXB7) has been reported to be aberrantly expressed in a variety of cancers, including melanoma [9], breast cancer [1015], gastric cancer [16, 17], liver cancer [18, 19], colorectal cancer [20] and esophageal cancer [21]. In addition, its expression has been correlated with clinical progression and poor outcome and may serve as a potential prognostic factor and therapeutic target [11, 14, 19, 20, 22, 23]. HOXB7 is involved in many of the major cellular processes that occur in cancer, including proliferation, invasion, migration, angiogenesis and the epithelial–mesenchymal transition (EMT) [24].…”
Section: Introductionmentioning
confidence: 99%
“…12 Overexpression of HOXB7 decreased the sensitivity of oral cancer cells to vincristine-induced apoptosis. 13 HOXB13 confers Tamoxifen resistance by directly downregulating ERa transcription and inducing IL-6 expression. 14 Previously, we found that HOXB7 was overexpressed in ESCC tissues compared with paired noncancerous mucosa, and it promoted oncogenic properties in ESCC cells through affecting cell proliferation, cell cycle and cell apoptosis, and presented negative survival significance in ESCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Knockdown of HOXC6 expression in multidrug resistance cells increased their sensitivity to paclitaxel via its regulation of MDR‐1 12 . Overexpression of HOXB7 decreased the sensitivity of oral cancer cells to vincristine‐induced apoptosis 13 . HOXB13 confers Tamoxifen resistance by directly downregulating ERa transcription and inducing IL‐6 expression 14 .…”
Section: Introductionmentioning
confidence: 99%